Carbohydrate Analogue Microarrays for Identification of Lectin‐Selective Ligands. (15th May 2017) - Hyun, Ji Young; Park, Cheol Wan; Liu, Yanna; Kwon, Daeun; Park, Seong‐Hyun; Park, Sungjin; Pai, Jaeyoung; Shin, Injae
Abstract: Fifty‐five mono‐ and disaccharide analogues were prepared and used for the construction of microarrays to uncover lectin‐selective ligands. The microarray study showed that two disaccharide analogues, 28′ and44′, selectively bind to Solanum tuberosum lectin (STL) and wheat germ agglutinin (WGA), respectively. Cell studies indicated that28′ and44′ selectively block the binding of STL and WGA to mammalian cells, unlike the natural ligand LacNAc, which suppresses binding of both STL and WGA to cells. Abstract : To uncover lectin‐selective ligands, 55 mono‐ and disaccharide analogues were synthesized and used for the construction of microarrays. Two disaccharide analogues identified by using the microarrays selectively bind two different lectins and selectively inhibit lectin binding to mammalian cells, unlike a natural ligand that blocks interactions of both lectins with cells.